Admission characteristics of pediatric chronic kidney disease - Eka Laksmi Hidayati; Partini Pudjiati Trihono (Paediatrica Indonesiana, 2011)
Background Chronic kidney disease (CKD) in children is a potentially fatal disease if left untreated. Early detection and treatment are important to slow progression to end-stage renal disease requiring dialysis.Objective We aimed to find characteristics of CKD patients at admission and evaluate factors associated with end-stage CKD (stage 5).Methods Our cross-sectional study was based on medical records of CKD patients aged less than 18 years in Cipto Mangunkusumo Hospital, Jakarta, from January 2007 to December 2009. Diagnosis and stages of CKD were based on the Kidney Disease Outcomes Quality Initiative (K/DOQI) criteria. Data on disease etiology, symptoms, nutritional status and laboratory tests were collected. Bivariate and multivariate analyses were performed to examine the association between end-stage CKD and its possible risk factors.Results Of the 142 cases eligible for analysis, 55% were boys. Subjects’ median age was 73.5 months (interquartile range of 23.5-122.5 months). Edema and recurrent fever were the two most frequent symptoms of CKD if diagnosed at stages 2-4, while breathlessness was the most frequent symptom of CKD if diagnosed at stage 5. The most common etiologies were glomerulonephritis (49.3%) and anomalies of the kidney and urinary tract (32.4%). Of our CKD subjects, 21.8% were in stage 5. Independent predictors of stage 5 CKD at presentation were hypertension (OR 3.88; 95% CI 1.17 to 12.87; P=0.026), urea level > 60 mg/dL (OR 39.11; 95%CI 4.86 to 314.74; P<0.001) and non-glomerulonephritis as the etiology (OR 6.51; 95%CI 2.12 to 19.92; P<0.001).Conclusion Glomerular disease was the most common cause of CKD in our study. Stage 5 CKD was present in 21.8% of subjects at admission and could be predicted by the presence of hypertension, high serum urea level, and non-glomerular disease as the etiology.